2001
DOI: 10.1103/physrevlett.86.1156
|View full text |Cite
|
Sign up to set email alerts
|

Search for Large Extra Dimensions in Dielectron and Diphoton Production

Abstract: We report a search for effects of large extra spatial dimensions in ppbar collisions at a center-of-mass energy of 1.8 TeV with the DZero detector, using events containing a pair of electrons or photons. The data are in good agreement with the expected background and do not exhibit evidence for large extra dimensions. We set the most restrictive lower limits to date, at the 95% confidence level, on the effective Planck scale between 1.0 TeV and 1.4 TeV for several formalisms and numbers of extra dimensions.Com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(22 citation statements)
references
References 30 publications
(28 reference statements)
1
21
0
Order By: Relevance
“…KLF6 is a tumor suppressor gene that is frequently inactivated by loss of heterozygosity (LOH), dysregulated alternative splicing, somatic mutation, and decreased expression in human cancer (9). In the field of lung cancer, several microarray studies have identified KLF6 (usually referred to in these reports as COPEB) as significantly dysregulated in tumors relative to normal tissue and/or as a contributor to gene signatures that predict patient survival (10)(11)(12). In addition, KLF6 expression was found to be significantly decreased in patient-derived lung adenocarcinoma samples compared with matched normal lung tissue in several recent studies by quantitative real-time PCR (qRT-PCR) (13).…”
Section: Introductionmentioning
confidence: 99%
“…KLF6 is a tumor suppressor gene that is frequently inactivated by loss of heterozygosity (LOH), dysregulated alternative splicing, somatic mutation, and decreased expression in human cancer (9). In the field of lung cancer, several microarray studies have identified KLF6 (usually referred to in these reports as COPEB) as significantly dysregulated in tumors relative to normal tissue and/or as a contributor to gene signatures that predict patient survival (10)(11)(12). In addition, KLF6 expression was found to be significantly decreased in patient-derived lung adenocarcinoma samples compared with matched normal lung tissue in several recent studies by quantitative real-time PCR (qRT-PCR) (13).…”
Section: Introductionmentioning
confidence: 99%
“…The lower limits at 95 % C.L. on the M D scale was given between 1.0 and 1.1 TeV with λ = 1 and −1 , respectively [21]. In (Fig.5), we see the exclusion bound for M D scale with respect to the softening scale and number of extra dimensions for the data.…”
Section: Collider Boundsmentioning
confidence: 71%
“…Present results are shown in Table 2, where it is also possible to find the prospects for LHC [5]. However, in contrast to branon direct production, current measurements by CMS or ATLAS detectors are not able to improve the limits obtained with data coming from HERA [24], Tevatron [25] and LEP [26].…”
Section: Colliders Searches At the Lhcmentioning
confidence: 99%